Microfilaria in cytological smears at rare sites coexisting with unusual pathology: A series of seven cases - Pantola, Chayanika (Medknow Publications & Media Pvt Ltd, 2012)
Filariasis is a major public health problem in India and microfilaria is sometimes seen during routine fine needle aspiration cytology (FNAC) smears, but it is very rare to find microfilaria coexistent with neoplastic lesions. Here we report a series of seven cases in which microfilaria is associated with neoplastic lesions. Out of these seven cases one is benign and six are malignant. Also we first time report the microfilaria coexistent with parotid pleomorphic adenoma, undifferentiated carcinoma thyroid and gall bladder carcinoma.